New resveratrol micelle formulation for ocular delivery: characterization and in vitro/in vivo evaluation. (1st December 2020) - Li, Mengshuang; Zhang, Ling; Li, Rong; Yan, Meixing
Abstract: Many eye diseases, such as corneal wound healing after injury, involve oxidative stress and inflammatory responses; however, many efficient natural antioxidants (e.g. resveratrol) have limited application in ophthalmology due to their poor solubility, low stability and poor ocular bioavailability. In this work, the aim was to formulate resveratrol into a micelle ophthalmic solution for efficient delivery to the eye. A Soluplus micelle ophthalmic solution containing resveratrol (Sol-Res) was formulated and optimized with a small and uniform dispersion in an ophthalmic solution. Sol-Res did not show any cell toxicity but promoted cell proliferation in both the short- and long-term cytotoxicity tests. The in vivo eye irritation test also verified the well ocular tolerance of the Sol-Res ophthalmic solution. The chemical stability of resveratrol in micelles in an aqueous solution was greatly improved over the free resveratrol solution, and Sol-Res also showed a good storage stability in the short-term storage stability test. Sol-Res showed improved in vitro passive permeation, in vitro cellular uptake, and in vivo corneal permeation over the free Res suspension solution. Furthermore, Sol-Res favored in vivo corneal wound healing, and the inhibition of key anti-inflammation mediators and the production of antioxidant factors in mRNA expression was observed in the Sol-Res treated wound healing corneas, suggesting that the mechanisms that regulate proinflammatory cytokines and oxidative stress might be involved in its therapeutic effect. Therefore, Sol-Res might be a promising candidate for further clinical application.